Spatial combined cable element for cable-supported bridges. Issue 1 (27th December 2018) - Wei, Jiandong; Guan, Manyu; Cao, Qi; Wang, Ruibin
Abstract : Purpose: The purpose of this paper is to analyze the cable-supported bridges more efficiently by building the finite element model with the spatial combined cable element. Design/methodology/approach: The spatial combined cable element with rigid arms and elastic segments was derived. By using the analytical solution of the elastic catenary to establish the flexibility matrix at the end of the cable segment and adding it to the flexibility matrix at the ends of the two elastic segments, the flexibility matrix at the end of the cable body is obtained. Then the stiffness matrix of the cable body is established and the end force vector of cable body is given. Using the displacement transformation relationship between the two ends of the rigid arm, the stiffness matrix of the combined cable element is derived. By assigning zero to the length of the elastic segment(s) or/and the rigid arm(s), many subdivisions of the combined cable element can be obtained, even the elastic catenary element. Findings: The examples in this field and specially designed examples proved the correctness of the proposed spatial combined cable element. Originality/value: The combined cable element proposed in this study can be used for the design and analysis of cable-stayed bridges. Case studies show that it is able to simulate cable accurately and could also be used to simulate the suspenders in arch bridges as well in suspension bridges.